Experimental and kinetic study of catalytic steam gasification of low rank coal with an environmentally friendly, inexpensive composite K2CO3–eggshell derived CaO catalyst. (1st February 2016) - Fan, ShuMin; Yuan, XiangZhou; Zhao, Liang; Xu, Li-Hua; Kang, Tae-Jin; Kim, Hyung-Taek
Highlights: The composite catalyst improved the yields of H2 -rich syngas. RPM was the best model to fit the experimental data. The composite catalyst performed higher catalysis ability at 800 and 900 °C. The composite catalyst reduced the activation energy about 51 kJ/mol. Abstract: The objective of this research was to study effects of composite catalysts (K2 CO3 and eggshell derived CaO) on gasification of Indonesian sub-bituminous KPU coal, which was conducted in a fixed bed reactor at atmospheric pressure. The effects of composite catalysts were evaluated from two sections: syngas compositions and reactivity. At 800 °C, the H2 yield of 1.34 mol/mol-C was obtained and the H2 fraction was 62 vol% when using the composite catalyst (15%K + 5%ES). Compared with only utilization of pure K2 CO3 and no catalyst, the composite catalyst (15%K + 5%ES) could increase the yields of H2 by 6% and 123%. In addition, a CO yield of 0.32 mol/mol-C was obtained by utilizing composite catalyst (15%K + 5%ES), and the CO yield increased by 19% compared with utilization of K2 CO3 and increased by 100% compared with no catalyst utilization. Through regression, kinetic parameters were determined from the random pore model (RPM), which provided a basis for design and operation of a realistic system. The RPM could adequately describe the conversion rate. Compared with results of non-catalytic steam gasification, the composite catalyst (15%K + 5%ES) was active in increasing the carbon conversion rate constant by more than three times within 700–900 °C due to its ability to reduce the activation energy of gasification by about 38%. It can be concluded that the composite catalyst not only enhances the catalytic effect, but also is environmentally friendly and inexpensive.